Partisanship, Sophistication, and Public Attitudes about Majority Rule and Minority Rights in Congress. Issue 4 (24th May 2016) - Park, Hong Min; Smith, Steven S.
Abstract : The balance between majority rule and minority rights is a central issue in the design and operation of democratic institutions and remains a contested issue in debates of policy‐making processes. Remarkably, public attitudes about this balance are not subjected to scholarly investigation. In this article, we report the findings of the first survey experiment in which the American public's attitudes about majority rule and minority rights in legislative bodies are explored. We find robust support for both majority rule and minority rights, discover that only a few Americans distinguish between the US House of Representatives and Senate in the application of these principles, and demonstrate that views of majority rule and minority rights can be moved once we introduce respondents to the partisan implications of procedural rules. Moreover, with conflicting theoretical expectations about the effect of political sophistication on attitudes about majority rule and minority rights, we find that higher levels of political sophistication are associated with stronger partisan effects on attitudes about the balance between majority rule and minority rights in Congress.